Yearbook on the African Union. Volume 4, (2023) - Engel, Ulf. (Leiden & Boston: Brill, 2023)
This is the fourth edition of the Yearbook on the African Union (YBAU). The YBAU is first and foremost an academic project that provides in-depth evaluation and analysis of the institution, its processes, and its engagements.
Includes bibliographical references and index.
Keywords: African Union. -- Yearbooks